2017
DOI: 10.1002/hon.2486
|View full text |Cite
|
Sign up to set email alerts
|

Role of BMI and age in predicting pathologic vertebral fractures in newly diagnosed multiple myeloma patients: A retrospective cohort study

Abstract: Vertebral fractures affect approximately 30% of myeloma patients and lead to a poor impact on survival and life quality. In general, age and body mass index (BMI) are reported to have an important role in vertebral fractures. However, the triangle relationship among age, BMI, and vertebral fractures is still unclear in newly diagnosed multiple myeloma (NDMM) patients. This study recruited consecutive 394 patients with NDMM at Taipei Veterans General Hospital between January 1, 2005 and December 31, 2015. Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…One study found that the decrease in BMI increased the vertebral fracture rate [21]. Other studies reported that lumbar spine fracture rate was 2.79 times higher for underweight individuals with BMI < 18.5 kg/ m 2 compared to those with BMI > 24 kg/m 2 [22]. Studies have reported that the reason for high fragility fracture rate in underweight individuals is related to muscle loss.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that the decrease in BMI increased the vertebral fracture rate [21]. Other studies reported that lumbar spine fracture rate was 2.79 times higher for underweight individuals with BMI < 18.5 kg/ m 2 compared to those with BMI > 24 kg/m 2 [22]. Studies have reported that the reason for high fragility fracture rate in underweight individuals is related to muscle loss.…”
Section: Discussionmentioning
confidence: 99%
“…(17) Other studies reported that lumbar spine fracture rate was 2.79 times higher for underweight individuals with BMI < 18.5 kg/m 2 compared to those with BMI > 24 kg/m 2 . (18) Studies have reported that the reason for high fragility fracture rate in underweight individuals is related to muscle loss.…”
Section: Discussionmentioning
confidence: 99%